A Paleogene trans-Antarctic distribution for Ripogonum (Ripogonaceae: Liliales)? - Carpenter, RJ; Wilf, P; Conran, JG; Ruben Cuneo, N (Coquina Press, 2014)
An impressive and growing list of biogeographically interesting plant and animaltaxa occur in Paleogene sediments of both southern Australia and southern SouthAmerica, indicating trans-Antarctic distributions during the warm past. Here, we providethe first evidence that the living, woody, Australasian monocot Ripogonum waspresent during the early Eocene of Patagonia, Argentina. Two fossil leaves are sufficientlywell preserved in overall shape, size, and fine venation details to be assigned tothe genus, being closely comparable to leaves of the extant species R. album and R.scandens and the recently described early Eocene species R. tasmanicum from Tasmania,Australia. The new species, R. americanum , is described. Overall, this evidencesuggests that Ripogonum had a significantly larger past range, includingAntarctica, during the early Paleogene, when Antarctica was much more closely connectedto both Tasmania and South America and high latitude climates were warm andwet. Ecologically, the South American Ripogonum was probably a scrambling vine inmesic forest and grew in association with a rich understory flora of ferns and angiosperms.